Extra tools in english lessons : voice, body language and sense of humor - Somensi, Júlia dos Santos (My University, 2018)
This paper reflects on the difference teachers could make by motivating their classroom with some simple adaptation regarding their behavior towards the students. The objective is to analyze three specific attitudes that may be connected to teachers with the ability to motivate their students to get involved in classes and keen on learning. The three specific approaches studied in this paper are vividness of voice, body language and sense of humor. Brown (2008) postulates motivating students is essential, starting from teachers demonstrating enthusiasm themselves. Having this in mind, the manner with which teachers use their voice and body language while talking to the class may have a great impact on students` perspective because it is through this kind of attitude that humans demonstrate and perceive emotions. The sense of humor comes as an emotional strategy to provide a comfortable environment and make students feel more relaxed and also a way for teachers to bond with the class, so they are not seen in a mechanic way. The emotional aspects involved in the learning process are defended by Morrison, who states that -learning must go through our emotional filter and our memories are composed of experiences that are linked to emotions? (MORRISON, 2008, p. 45). As a result, this paper makes a reflexion on the Brazilian educational system and proposes some tips for new professionals to have a productive first year as educators, regarding the factors aforementioned (sic).
Este artigo reflete sobre a diferença que os professores poderiam fazer ao motivar sua sala de aula com algumas adaptações simples considerando seu comportamento em relação aos alunos. O objetivo é analisar três comportamentos específicos que podem estar relacionados aos professores com a capacidade de motivar seus alunos a se envolverem nas aulas. As três abordagens específicas estudadas neste trabalho são a vivacidade da voz, a linguagem corporal e o senso de humor. Brown (2008) postula que motivar os alunos é essencial a partir de professores que demonstram entusiasmo. Tendo isso em mente, a maneira como os educadores usam a voz e a linguagem corporal ao falar com a turma pode ter um grande impacto na perspectiva dos alunos, porque é através desse tipo de atitude que os humanos demonstram e percebem emoções. O senso de humor surge como uma estratégia emocional para proporcionar um ambiente mais leve e fazer com que os alunos se sintam mais relaxados e também uma forma de os professores se relacionarem com a turma, para que não sejam vistos de forma mecânica. Os aspectos emocionais envolvidos no processo de aprendizagem são defendidos por Morrison, que afirma que -a aprendizagem deve passar pelo nosso filtro emocional e as nossas memórias são compostas de experiências que estão ligadas às emoções? (MORRISON, 2008, p. 45). Como resultado, este trabalho faz uma reflexão sobre o sistema educacional brasileiro e propõe algumas dicas para que os novos profissionais tenham um primeiro ano produtivo como educadores, considerando os fatores supracitados (sic).
Keywords: Motivation in education; Voice; Body language; High schools; English language - Study and teaching